Patients’ perceptions of home-based imaging diagnostics: A qualitative study - Lorena Jorge Lorenzi; Giovana Fondato Costa; Helianthe Kort; Paula Costa Castro (PLoS ONE, 2026)
Expanding access to diagnostic services through home-based imaging represents a promising strategy to reduce barriers to healthcare, particularly by eliminating the need for patient travel. For this model to be viable, diagnostic equipment must be portable, and its success depends in part on patient acceptance. Despite the growing implementation of home imaging services, there is a lack of evidence in the literature regarding patient perceptions of this modality across different exam types. Therefore, the present study aimed to assess the perceptions of patients who underwent home-based imaging diagnostics. This qualitative interview study was conducted with patients who underwent home-based imaging diagnosis. The interviews were conducted by phone between May and July 2024, with up to three contact attempts. When necessary, a proxy answered on behalf of the patient. Aspects such as positive and negative points, reliability, preference, preparation, and quality of care were analyzed. The interviews were recorded, transcribed, and analyzed using inductive analysis. Thirty-four patients and their proxies participated in the study, with the majority of patients being older adults. Four types of imaging exams were performed in the home setting. Participants’ perceptions were predominantly positive, emphasizing the convenience of avoiding travel, the high quality of care provided, confidence in the accuracy of the exams, and the quality of the equipment used. However, some concerns emerged, such as fear in receiving professionals at home, the need for faster result access, and better home infrastructure for exams. The insights gained from this study provide valuable guidance for the development of regulatory frameworks and operational strategies for home-based imaging services. By addressing the identified needs and concerns of end users, these findings can support the improvement of public policies, while also informing on how to effectively plan and manage such services to enhance satisfaction, adherence, and broader implementation.